A-186 Injury Mechanism, Premorbid Intelligence, and Psychological Outcomes Post Mild Traumatic Brain Injury. (17th August 2022) - DeBoer, Adam B; Amitrano, Nicholas R; Pyykkonen, Ben A; Balloun, Bailey A; Barwegen, Kearston C
Abstract: Objective: This study aimed to explore psychological outcomes of individuals who sustained a mild traumatic brain injury (mTBI) as impacted by injury mechanism and premorbid intelligence. Cognitive outcomes post mTBI are well-researched, and the impact of premorbid intelligence has routinely been shown in the literature to impact cognitive outcomes, but type of injury and psychiatric outcomes have received much less attention. Method: All 108 participants were referred for outpatient neuropsychological evaluation following presentation to the emergency room with head injury. A multivariate analysis of covariance (MANCOVA) was used to explore the relationship of injury mechanism (motor vehicle accident (MVA) or fall) to psychological outcomes as measured by the major depressive disorder, generalized anxiety disorder, alcohol abuse/dependence, drug abuse/dependence, and posttraumatic stress disorder (PTSD) scales on the Psychiatric Diagnostic Screening Questionnaire (PDSQ). Premorbid intelligence as assessed using WRAT—4 Reading was the covariate. A binary logistic regression was also used to determine which PDSQ scales were predictors of injury mechanism. Results: In the MANCOVA analysis, alcohol abuse/dependence was the sole variable approaching significance (p = .068). The logical regression equation model accurately classified 98.9% of MVA cases, wherein alcohol abuse/dependence emerged as the lone significant predictor (p = .028). Conclusions: Contrary to literature on cognitive outcomes, premorbid intelligence was not associated with psychological outcomes post mTBI. Independent of injury mechanism, no significant differences among PDSQ outcome scales were discovered. Finally, those with mTBI due to MVA had a higher probability of alcohol abuse/dependence compared to those with those suffering a mTBI from a fall.